2015
DOI: 10.1177/1748048515601560
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating distant suffering: How can news media discursively invite the audience to care?

Abstract: Several scholars have identified an important emotional role in news media's covering of international disasters; inviting the audience to care for people in need who are not like us. This article addresses the question of how news media can attribute a local sense of relevance to global suffering by focusing on the journalistic practice of domestication. Following a case-based methodology, we investigate how two Belgian television stations have domesticated international disasters in 2011. As the study shows,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…These discursive modes of domesticating international news were first explicitly linked to mediated distant suffering when we uncovered four dominant strategies of domestication employed by news producers to invite the audience to care (Joye, 2015). First, we found that journalists domesticate distant suffering by selecting emotionally narrated stories or eyewitness accounts of compatriots who were affected by the foreign event (emotional domestication).…”
Section: Domesticating Distant Sufferingmentioning
confidence: 99%
See 4 more Smart Citations
“…These discursive modes of domesticating international news were first explicitly linked to mediated distant suffering when we uncovered four dominant strategies of domestication employed by news producers to invite the audience to care (Joye, 2015). First, we found that journalists domesticate distant suffering by selecting emotionally narrated stories or eyewitness accounts of compatriots who were affected by the foreign event (emotional domestication).…”
Section: Domesticating Distant Sufferingmentioning
confidence: 99%
“…Although domestication is also defined as 'the discursive adaptation of news from 'outside' the nation-state so as to make it resonate with a national audience as it is perceived' (Olausson, 2014: 711, emphasis added), we can easily understand why most research has chosen to focus on the production side and on the journalists whose discursive practices are investigated through textual analysis (Alasuutari et al, 2013;Olausson, 2014;Joye, 2015).…”
Section: Domesticating Distant Sufferingmentioning
confidence: 99%
See 3 more Smart Citations